Age‐dependent alterations of the NMDA receptor developmental profile and adult behavior in postnatally ketamine‐treated mice. Issue 3 (17th September 2014) - Lecointre, Maryline; Vézier, Claire; Bénard, Magalie; Ramdani, Yasmina; Dupré, Nicolas; Brasse‐Lagnel, Carole; Henry, Vincent J.; Roy, Vincent; Marret, Stéphane; Gonzalez, Bruno J.; Jégou, Sylvie; Leroux‐Nicollet, Isabelle
ABSTRACT Ketamine is a NMDA receptor (NMDAR) antagonist used in pediatric anesthesia. Given the role of glutamatergic signaling during brain maturation, we studied the effects of a single ketamine injection (40 mg/kg s.c) in mouse neonates depending on postnatal age at injection (P2, P5, or P10) on cortical NMDAR subunits expression and association with Membrane‐Associated Guanylate Kinases PSD95 and SAP102. The effects of ketamine injection at P2, P5, or P10 on motor activity were compared in adulthood. Ketamine increased GluN2A and GluN2B mRNA levels in P2‐treated mice without change in proteins, while it decreased GluN2B protein in P10‐treated mice without change in mRNA. Ketamine reduced GluN2A mRNA and protein levels in P5‐treated mice without change in GluN2B and GluN1. Ketamine affected the GluN2A/PSD95 association regardless of the age at injection, while GluN2B/PSD95 association was enhanced only in P5‐treated mice. Microdissection of ketamine‐treated mouse cortex showed a decrease in GluN2A mRNA level in superficial layers (I–IV) and an increase in all subunit expressions in deep layers (V–VI) in P5‐ and P10‐treated mice, respectively. Our data suggest that ketamine impairs cortical NMDAR subunit developmental profile and delays the synaptic targeting of GluN2A‐enriched NMDAR. Ketamine injection at P2 or P10 resulted in hyperlocomotion in adult male mice in an open field, without change in females. Voluntary running‐wheel exercise showed age‐ and sex‐dependent alterations of the mouse activity, especially during the dark phase. Overall, a single neonatal ketamine exposure led to short‐term NMDAR cortical developmental profile impairments and long‐term motor activity alterations persisting in adulthood. © 2014 Wiley Periodicals, Inc. Develop Neurobiol 75: 315–333, 2015